Archaeological research in the former municipalities of Koivisto and Kuolemajarvi, Karelian Isthmus in 2003: results and observations - Nordqvist, Kerkko; Seitsonen, Oula (The Finnish Antiquarian Society, 2021)
This paper presents the archaeological studies conducted by Finnish and Russian researchers in 2003 in the former municipalities of Koivisto and Kuolemajarvi in the Karelian Isthmus. The environmental history and archaeological research history of the area are also summarized. Short surveys and small-scale test excavations at three sites revealed the long time span and versatility of the prehistoric habitation in the area. The oldest sites located in the surveys seem to date from the Mesolithic period. A test excavation was carried out at one of these sites. The whole Neolithic period also seems to be represented, and one of the test-excavated sites dates to the Early Metal period based on the presence of a Textile-impressed Ware pot broken in situ. The area holds high research potential for further prehistoric studies.